Gensyn med Danmarks største blomsterforretning - Wowk Vestergaard, Anna (Den Gamle By: Danmarks Købstadmuseum (Årbog), 2024)
Gottlieb Blomster flyttede i 1966 til nye lokaler på Åboulevarden i Aarhus. Her genåbnede den som en topmoderne butik indrettet efter tidens trends. Butikken lukkede i 1975 og er nu genskabt i Den Gamle By, hvor den er med til at fortælle historien om, hvordan velstandsstigningen i løbet af 1960’erne blev afspejlet i et stigende salg af ting til hjemmet. Blomster og grønne planter blev sammen med moderigtigt tilbehør en måde at følge moden i indretningstendenserne på. Museumsinspektør Anna Wowk Vestergaard planter historien om Gottlieb Blomster. The Biggest Florist Shop in Denmark The florist shop Gottlieb Blomster opened on Easter 2023 in Den Gamle By’s 1974 pedestrian street. The original Gottlieb Blomster moved to new premises in Aarhus in 1966 and reopened as a cutting edge store. The shop tells the story of how growing wealth in the 1960s led to an increase in sales of products for the home. Green plants and dried flowers became fashionable, and the florists combined them with accessories made of ceramics and glass, so that the furnishing trends could be followed without the need to replace the entire living room. As a brand new offer, Gottlieb Blomster had an express purchase section that could compete with the supermarkets selling small house plants. It was a great success and other florists copied the concept. Despite this, the store had to close in 1975. Fortunately for us, the Gottlieb Family stored the furnishings and stock in a basement where it remained as a time capsule until 2012 when it was brought to Den Gamle By. Once again home accessories fill the shop along with the popular house plants of the 1970s.